2011
DOI: 10.1007/s11627-011-9353-8
|View full text |Cite
|
Sign up to set email alerts
|

Pluronic F-68: an answer for shoot regeneration recalcitrance in microspore-derived Brassica napus embryos

Abstract: Recalcitrance to tissue culture is observed in some genotypes of Brassica napus. Several studies have confirmed that Pluronic F-68 has growth-promoting effects on numerous tissue types. This work investigated the effect of the non-ionic surfactant Pluronic F-68 at four concentrations (0.1%, 0.25%, 0.5%, and 1% (w/v)) on the responsiveness of recalcitrant B. napus lines to tissue culture. Microspores from seven populations of B. napus were cultured on Nitsch and Nitsch medium with this compound. The embryos obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Aside from protein abundance in plants, esterase could be used to determine cell viability. Several studies have utilized the changes in esterase activity as a marker to study the growth characteristics and cell viability in plants (Amano et al, 2003;Tamás et al, 2005;Víteček et al, 2007). In a way, a decrease in esterase activity in plants corresponds with the decrease in cell viability in plants.…”
Section: General Function Difference In Protein Abundancementioning
confidence: 99%
See 2 more Smart Citations
“…Aside from protein abundance in plants, esterase could be used to determine cell viability. Several studies have utilized the changes in esterase activity as a marker to study the growth characteristics and cell viability in plants (Amano et al, 2003;Tamás et al, 2005;Víteček et al, 2007). In a way, a decrease in esterase activity in plants corresponds with the decrease in cell viability in plants.…”
Section: General Function Difference In Protein Abundancementioning
confidence: 99%
“…Some of the commonly used growth additives in plant tissue culture include Pluronic F-68 (PF-68), lignosulfonate, silver nitrate, silicon, coconut, and gibberellic acid (Biswas and Mandal, 2007 ; He et al, 2013 ; Yildirim and Turker, 2014 ; Irshad et al, 2018 ; Wan Abdullah et al, 2020 ). PF-68 is a non-ionic, copolymer surfactant that has been employed as an additive in both in vitro animal and plant cultures (Meier et al, 1999 ; Barbulescu et al, 2011 ). PF-68 has been widely utilized in animal cell suspension culture to protect and repair damaged cells from constant sparging and agitation (Meier et al, 1999 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their interaction with human cells is also well studied (reviewed in Jarak et al 2020), however, little is known about plant cells. Nevertheless, there are reports demonstrating that at specific experimental conditions, Pluronic F-68 has growth-stimulating effects on protoplasts (Kumar et al 1992, Anthony et al 1997, plant cell/ tissue cultures (Kumar et al 1992, Iordan-Costache et al 1995, Khehra et al 1995, Anthony et al 1996, Cancino et al 2001, Lee and Kim 2002, Kaparakis and Alderson 2003, Khatun et al 2003, Kok et al 2021, and microspore cultures (Barbulescu et al 2011). The effect of Pluronics on intact plants of large crabgrass was studied by Nalewaja et al (1998) who showed that Pluronic P85 was one of the most effective adjuvants tested (among five types of Pluronic polymers) for the reduction of nicosulfuron herbicide phytotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…De-Xian Kok et al [34] demonstrated in their study that PF-68 has growth-stimulating effects without being dependent on the presence of plant hormones. The optimal concentration of PF-68 has improved the absorption of nutrients in plant tissue demonstrating the many beneficial effects of tissue regeneration and proliferation in recalcitrant species in vitro [34][35][36][37] as well as in P. edulis, P. giberti and P. mollissima [32].…”
Section: Introductionmentioning
confidence: 99%